Pengaruh Motivasi Kerja Dan Beban Kerja Terhadap Retensi Karyawan Pada Rumah Sakit Pertamina Jaya Jakarta Pusat - Endang Herawan; Indri Indirasari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the Effect of Work Motivation and Workload on Employee Retention at Pertamina Jaya Hospital, Central Jakarta. This study uses an associative quantitative research type. The quantitative approach emphasizes objective measurement of social phenomena using numerical data which is then analyzed statistically. The results of a simple regression show the equation: Y=34.517+0.186X_1 The regression coefficient is 0.186 with Sig. 0.009 0.05 means that work motivation has a positive and significant effect on employee retention. The Pearson correlation value of 0.193 indicates a very weak but significant relationship. This means that the higher the work motivation, the employee retention tends to increase. The results of a simple regression produce: Y=46.079+0.122X_2 The regression coefficient is 0.122 with Sig. 0.006 >0.05 indicates that workload has a negative and significant effect on employee retention. The correlation value of 0.202 indicates a strong but significant relationship. The results of multiple regression show: Y=38.556+0.172 The F test produces F count of 7.016 with Sig. 0.001<0.05, meaning that work motivation and workload simultaneously have a significant effect on employee retention. Motivation increases retention, while workload decreases it.